2015
DOI: 10.1161/jaha.114.001626
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate at Hospital Discharge in Patients With Heart Failure Is Associated With Mortality and Rehospitalization

Abstract: Background Whether heart rate upon discharge following hospitalization for heart failure is associated with long‐term adverse outcomes and whether this association differs between patients with sinus rhythm (SR) and atrial fibrillation (AF) have not been well studied. Methods and Results We conducted a retrospective cohort study from clinical registry data linked to Medicare claims for 46 217 patients participating in Get With The Guidelines ® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 34 publications
10
60
1
2
Order By: Relevance
“…Furthermore, in contrast to the findings in patients with heart failure and SR, the association between discharge HR and all-cause readmission and the composite outcome (all-cause mortality or all-cause readmission) were not statistically significant, suggesting that in patients with AF, HR might be of lesser importance over the long term. 28 These support the notion that patients with HF and AF are at intrinsically higher risk for death, and this increased baseline risk attenuates an HR effect. However, it is noteworthy to mention that this study is different from our study because it included patients with both HFrEF and heart failure with preserved EF and only patients aged >65 years.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, in contrast to the findings in patients with heart failure and SR, the association between discharge HR and all-cause readmission and the composite outcome (all-cause mortality or all-cause readmission) were not statistically significant, suggesting that in patients with AF, HR might be of lesser importance over the long term. 28 These support the notion that patients with HF and AF are at intrinsically higher risk for death, and this increased baseline risk attenuates an HR effect. However, it is noteworthy to mention that this study is different from our study because it included patients with both HFrEF and heart failure with preserved EF and only patients aged >65 years.…”
Section: Discussionsupporting
confidence: 60%
“…It might be that this intrinsically higher baseline risk explains the attenuation of the association for patients with AF at HRs <100 beats per minute. In a recently published study, 28 in patients with heart failure with concomitant AF, although early (0-30 days) and late (31-365 days) associations between HR and mortality were statistically significant at rates ≥75 beats per minute, the magnitude of this association decreased over the late term. Furthermore, in contrast to the findings in patients with heart failure and SR, the association between discharge HR and all-cause readmission and the composite outcome (all-cause mortality or all-cause readmission) were not statistically significant, suggesting that in patients with AF, HR might be of lesser importance over the long term.…”
Section: Discussionmentioning
confidence: 89%
“…The GWTG‐HF risk score consists of 7 commonly available clinical variables, and it can be used to establish the probability of in‐hospital mortality 15, 17. From the GWTG‐HF registry cohort, several studies have reported the risk of mortality and rehospitalization after discharge 24, 25, 26. There were no reports that revealed the significance of risk prediction beyond 1 year, and our present study demonstrated that the GWTG‐HF risk score could be a useful predictor for risk stratification for several years after discharge in patients with HF, both HFpEF or HFrEF.…”
Section: Discussionmentioning
confidence: 99%
“…Observational cohorts and controlled trials have shown a consistent correlation between elevated HR and morbidity and mortality in general and HF with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF) specifically. [3][4][5][6][7][8][9][10][11] In the Get With The Guidelines-Heart Failure registry, resting HR ≥70 bpm in sinus rhythm on hospital admission was associated with increased in-hospital mortality, and resting HR on discharge predicted 1-year hospital readmission and mortality. 7,12 These data, however, do not distinguish whether HR is a risk factor or a modifiable therapeutic target.…”
Section: Hr Management In Hfmentioning
confidence: 99%